Reproductive Diseases in Farmed Rabbit Does - Joan Maria Rosell; Luis Fernando de la Fuente; María Teresa Carbajo; Xosé María Fernández (Animals, 2020)
In this study, we determined the occurrence of reproductive diseases in does on 1373 visited farms in Spain and Portugal, between 1994 and 2019. The retrospective information obtained was entered in a database classified as follows: apparent infertility (≤70% pregnancy rate), abortions (≥2% of serviced does), high fetal death risk at parturition (≥10%) or dystocia, amongst others. Infertility was the reason for 181 visits. The median of prevalence of apparent infertility in these cases was 35% (minimum to maximum: 25–90%) and the mean, 37.4%. We performed a prospective study to determine risk factors at the individual and farm level, with a second database corresponding to 2014–2019. We carried out pregnancy checks, assessed sanitary status and body condition, and recorded the age of 17,297 rebred lactating does on 142 farms. The median size of the farms was 800 does, and the examined cohorts, 350 does. Predisposing risk factors for infertility were observed: e.g., mastitis had an effect. During the 5-year study, we made a third database with the results from 190,508 does palpated by producers in a subset of 134 farms. In this case, the median of the prevalence of apparent infertility was 14.5% (minimum to maximum: 4.1–50%), which could be considered baseline occurrence when monitoring the theriogenology of rabbit doe farms. Reproductive rhythm was an enabling risk factor: does serviced ≤25 d postpartum were less fertile than at ≥32 d. We made a database with the body condition score (BCS) on a linear scale from 1 (emaciated) to 9 (obese). The pregnancy rate (PR) of underweight and borderline does (4/9) was 73.1%. The PR of overweight and borderline does (6/9) was 82.6% and those classified with a mean BCS (5/9): PR = 79.3%. We may infer that the optimum BCS for reproduction is 6/9, rather than 5/9. Some changes in female rabbit health and husbandry to improve reproductive performance and welfare are highlighted.